Manajemen Pendidikan Full Day School dalam Pembentukan Karakter Siswa: Studi di Sekolah Dasar Islam Terpadu Nurul Ilmi Medan Estate - Khuzaimah, Khuzaimah; Akrim, Akrim; Prasetia, Indra (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2025)
This study seeks to investigate the administration of full-day school education in influencing the development of character students of Nurul Ilmi Medan Estate Integrated Islamic Elementary School. This research uses a qualitative method. The results of the study show that: First, the implementation of full day school education management in the formation of student character, including: 1) the process of implementing student activities, 2) the method of implementing full day school management for students, and 3) the full day school management program in the development of students' character. The application of comprehensive day school administration in molding student character has been successful. This is evident through the significant amount of time dedicated to shaping pupils' character who are religious, disciplined, independent, creative, friendly and responsible. Furthermore, there is an extracurricular program, where students can develop their interests and talents, and there is also a program to instill religious values, such as students are disciplined in carrying out worship. Second, efforts to implement a Full-day school management method shapes student character SD IT Nurul Ilmi through the application of values based on the teachings of the Quran and Sunnah which are trained with disciplined and responsible habits so that it becomes a routine that is expected to have an influence on the formation of student character. Third, the advantages of full day school management at SD IT Nurul Ilmi Medan Estate include good quality teachers, very beautiful school locations, facilities and infrastructure, good service in dealing with students and parents, and parents feel safe and comfortable because children are well controlled. Meanwhile, weaknesses include some children feeling bored because they are at school every day, students feel that they are not free to adapt outside of school and lack of evaluation of monthly reports reported by teachers every month.